Numerical methods for simulation and optimization of piecewise deterministic Markov processes : application to reliability /: application to reliability. (2016) - Saporta, Benoîte de; (Mathematician), Dufour, François; (Lecturer in mathematics), Zhang, Huilong
No abstract available